PCR-mediated repeated chromosome splitting in Saccharomyces cerevisiae - Minetaka Sugiyama; Shigehito Ikushima; Toshimasa Nakazawa; Yoshinobu Kaneko; Satoshi Harashima (BioTechniques)
Chromosome engineering is playing an increasingly important role in the functional analysis of genomes. A simple and efficient technology for manipulating large chromosomal segments is key to advancing these analyses. Here we describe a simple but innovative method to split chromosomes in Saccharomyces cerevisiae, which we call PCR-mediated chromosome splitting (PCS). The PCS method combines a streamlined procedure (two-step PCR and one transformation per splitting event) with the Cre/loxP system for marker rescue. Using this novel method, chromosomes I (230 kb) and XV (1091 kb) of a haploid cell were split collectively into 10 minichromosomes ranging in size from 29-631 kb with high efficiency (routinely 80%) that were occasionally lost during mitotic growth in various combinations. These observations indicate that the PCS method provides an efficient tool to engineer the yeast genome and may offer a possible approach to identify minimal genome constitutions as a function of culture conditions through further splitting, followed by combinatorial loss of minichromosomes.